2009
DOI: 10.1128/jcm.00034-09
|View full text |Cite
|
Sign up to set email alerts
|

Association between Contaminated Faucets and Colonization or Infection by Nonfermenting Gram-Negative Bacteria in Intensive Care Units in Taiwan

Abstract: This study was designed to determine the strength of the association between the isolation of nonfermentative gram-negative bacilli (NFGNB) from tap water faucet aerators and the prevalence of colonization or infection of patients in intensive care units (ICUs). Surveillance cultures were obtained during a 4-month period from 162 faucet aerators located in seven different ICUs. The prevalence of colonization or infection of ICU patients with NFGNB was determined by prospective surveillance during the same peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 25 publications
1
42
0
2
Order By: Relevance
“…Seven intensive care units, including a neurosurgical ICU, a surgical ICU, a cardiac surgical ICU, a pediatric ICU, two medical ICUs, and a respiratory care unit, were sampled for the presence of NFGNB. PFGE and electrokaryotyping analyses revealed no similarity between the S. maltophilia, P. aeruginosa, B. cepacia, and A. xylosoxidans isolates from faucets and the corresponding species of clinical isolates (355). That study also reported a strong positive correlation between the presence of NFGNB in the hospital tap water and the prevalence of waterborne NFGNB in ICU patients (355).…”
Section: Linking Clinical Isolates To Sourcesmentioning
confidence: 84%
See 2 more Smart Citations
“…Seven intensive care units, including a neurosurgical ICU, a surgical ICU, a cardiac surgical ICU, a pediatric ICU, two medical ICUs, and a respiratory care unit, were sampled for the presence of NFGNB. PFGE and electrokaryotyping analyses revealed no similarity between the S. maltophilia, P. aeruginosa, B. cepacia, and A. xylosoxidans isolates from faucets and the corresponding species of clinical isolates (355). That study also reported a strong positive correlation between the presence of NFGNB in the hospital tap water and the prevalence of waterborne NFGNB in ICU patients (355).…”
Section: Linking Clinical Isolates To Sourcesmentioning
confidence: 84%
“…PFGE and electrokaryotyping analyses revealed no similarity between the S. maltophilia, P. aeruginosa, B. cepacia, and A. xylosoxidans isolates from faucets and the corresponding species of clinical isolates (355). That study also reported a strong positive correlation between the presence of NFGNB in the hospital tap water and the prevalence of waterborne NFGNB in ICU patients (355). The findings of that study suggest that alternatives to the use of hospital tap water should be considered, including disinfection of the water supply, point-of-use water filtration, and the use of sterile water.…”
Section: Linking Clinical Isolates To Sourcesmentioning
confidence: 92%
See 1 more Smart Citation
“…A. xylosoxidans is an aerobic, motile, Gram-negative bacillus that is a nonfermenter and is catalase and oxidase positive. A. xylosoxidans is ubiquitous in aqueous environments and has been associated with well water (36), tap water (17,43), and swimming pools (33) as well as environmental bodies of water (41). It is also a prevalent nosocomial colonizer and has been isolated from multiple types of aqueous solutions found in the health care setting, such as nonbacteriostatic saline (24), dialysis solutions (33), contact lens solutions (15), intravenous CT contrast solutions (32), chlorhexidine gluconate solutions (35), and ultrasound gel (28).…”
Section: Case Reportmentioning
confidence: 99%
“…It is also a prevalent nosocomial colonizer and has been isolated from multiple types of aqueous solutions found in the health care setting, such as nonbacteriostatic saline (24), dialysis solutions (33), contact lens solutions (15), intravenous CT contrast solutions (32), chlorhexidine gluconate solutions (35), and ultrasound gel (28). A. xylosoxidans also colonizes fomites such as mechanical ventilators (6), neonatal incubators (25,29), faucet aerators (17,43), intravenous catheters (1,17,20,24), epidural catheters (30), urinary catheters (29), intravascular pressure transducers (17), pacemaker leads (2,26,33,36), and extracorporeal membrane oxygenation machines (21).…”
Section: Case Reportmentioning
confidence: 99%